Serum Inflammatory Factors and Oxidative Stress Factors Are Associated With Increased Risk of Frailty and Cognitive Frailty in Patients With Cerebral Small Vessel Disease - Mu, Lei; Jiang, Limin; Chen, Juan; Xiao, Mei; Wang, Wei; Liu, Peipei; Wu, Jialing (Frontiers in Neurology, 2022)
Objective: To study the correlation between serum inflammatory factors, oxidative stress factors and frailty, and cognitive frailty in patients with cerebral small vessel disease (CSVD). Methods: A total of 281 patients with CSVD were selected from Tianjin Huanhu Hospital and Inner Mongolia People's Hospital from March 2019 to March 2021. CSVD was diagnosed by MRI. The FRAIL scale was used to evaluate the frailty of patients. Patients with CSVD with frailty and MMSE score <27 were considered to have cognitive frailty. Patients with non-cognitive frailty were included in the control group. The Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE) were used to evaluate the cognitive function of patients with CSVD. The serum interleukin 6 (IL-6), tumor necrosis factor-alpha (TNF-α), matrix metalloproteinase 3 (MMP-3), superoxide dismutase (SOD), and malondialdehyde (MDA) of patients with CSVD were detected. The correlation between blood inflammatory factors and oxidative stress factors with the frailty and cognitive frailty patients of CSVD were analyzed. Univariate and multivariate logistic regression were used to analyze the correlation between cognitive frailty and CSVD. Results: Among the patients with CSVD selected in this study, female patients and older patients had a higher proportion of frailty (p < 0.001). In the Frail group, MoCA score and MMSE score were significantly lower than in the Pre-Frail and Robust groups, Hamilton Depression Scale (HAMD) and Hamilton Anxiety Scale (HAMA) scores were significantly higher than the Pre-Frail and Robust groups, and the differences were statistically significant (p < 0.05). Serum CRP, IL-6, TNF-α, MMP-3, and MDA levels in the Frail group were higher, but SOD levels were lower. The levels of serum CRP, IL-6, TNF-α, MMP-3, and MDA in patients with CSVD in the Cognitive Frailty group were significantly higher than those of the Control group, while the levels of SOD were significantly lower than those of the Control group, and the differences were significant (p < 0.001). The results of univariate and multivariate logistic regression analysis showed that CRP, TNF-α, MMP-3, and MDA levels were associated with cognitive frailty in patients with CSVD (p < 0.05). Conclusion: The increase of serum CRP, TNF-α, MMP-3, and MDA levels are significantly related to the increased risk of frailty and cognitive frailty in patients with CSVD.